Recent improvements in X-ray spectrometry measurements performed at the MADERE facility dedicated to reactor dosimetry requirements - Tisseur David; Domergue Christophe; Destouches Christophe; Philibert Hervé; Pepino Alexandra; Bonora Jonathan; Thiollay Nicolas; Lépy Marie Christine; Riffaud Jonathan; Hernández-Elvira Víctor (EPJ Web of Conferences)
CEA/Cadarache operates the MADERE facility dedicated to measuring the activity of radionuclides generated during the irradiation of specific dosimeters made of hyper-pure materials. This facility is equipped with seven spectrometers, two of which are dedicated to the detection of radionuclides that emit X-rays. The laboratory that operates the MADERE facility processes solid-state rhodium and niobium dosimeters, which emit X-rays of 20 keV and 16 keV respectively. In recent years, there have been significant improvements in nuclear decay data, leading to better measurement of these two X-ray emitters. A joint LDCI and LNHB thesis, defended in 2018, produced major advances (for example self-attenuation corrections for 93mNb and 103mRh). The most significant achievements and outlooks are presented in this paper for the both niobium and rhodium dosimeters.